Optimization Scheme of Offshore Steel Structures - Mastanzade, Nıjat (İstanbul Kültür Üniversitesi Yayınları, 2002)
Deniz petrol yapıların optimizasyonu için son elemanlar üsulu, Reileigh üsulu ve Lagrange katsaylar üsullları kullanılıp. Bu problem yerdeğişme, dinamik Rijitlik ve stabilite sınırı şartlı problemleri çözülüp.

The finite elements method, Reyleigh correlation and Lagrange multipliers method for the problem of optimization of offshore platform. This problem is calculated by stability, dynamic stiffness and displacement requirements
Keywords: dynamic; dinamik; optimization; optimizasyon; stiffness; katılık; displacement; deplasman; offshore; açık deniz